Educational Synergies Informing Museum/Informal and School/Formal Experiences - Laura Rachel Fattal (Journal of Pedagogical and Teacher Professional Development, 2025)
This article advocates for the educational importance of the synergy between museum/informal and school/formal pedagogical praxis and perspectives. Realigning learning from a curricular/aesthetic focus on art historical constructs to generate cognition through pedagogies of discovery, risk-taking, imaginative, and critical thinking has energized teaching in both museums and schools. The significance of this research article stems from its timely focus on the valuable but often unacknowledged synergetic educational practices in both museums and schools. The discussion includes: a) Museum pedagogical practices, b) Interactive exemplar museum/school educational praxis, c) Transdisciplinary curricula, d) Navigating online resources, e) Expanding creative technologies, and f) Inquiry and discovery as life-long educational goals. From cabinets of curiosities, to palaces of wonder, museums are no longer solely repositories for objects but spaces of aesthetic-lived experiences for students to create dialogue and make connections with their everyday world.